Shoulder Arthroplasty Outcomes in Patients With Multiple Reported Drug Allergies: Does Number of Drug Allergies Have an Effect on Outcome?. Issue 11 (14th November 2016) - Rosenthal, Brett D.; Knesek, Michael J.; Kahlenberg, Cynthia A.; Mai, Harry; Saltzman, Matthew D.
Background: The presence of multiple allergies has been correlated with worse outcomes for patients undergoing hip and knee arthroplasty, but the effect of allergies has not yet been elucidated with respect to shoulder arthroplasty. Purpose/Hypothesis: The purpose of this study is to identify any discrepancies in shoulder arthroplasty outcomes with respect to reported drug allergies. We hypothesized that patients with multiple drug allergies would have inferior outcomes. Study Design: Cohort study; Level of evidence, 3. Methods: Included in the analysis were a single surgeon's cases between 2009 and 2014 of primary total shoulder arthroplasty with a minimum of 180 days of follow-up. Cases with fracture as the indication were excluded. Preoperative and postoperative metrics included visual analog scale (VAS) for pain, forward flexion range of motion, and Simple Shoulder Test (SST) results, and postoperative patient satisfaction scores were also collected. Chi-square and 1-way analysis of variance with Tukey post hoc analyses were performed when appropriate. Results: A total of 98 patients were included (no allergies, n = 51; single allergy, n = 21; multiple allergies, n = 26). The proportion of females was greater with increasing number of allergies (no allergies, 31%; single allergies, 47%; multiple allergies, 88%; Pearson χ 2 = 22.5; P < .0001). Both preoperatively and postoperatively, no difference was found between cohorts with respect to SST score, VAS score, or forward flexion. There was also no difference in postoperative satisfaction between cohorts. No difference between cohorts was identified when comparing the pre- to postoperative change in SST scores, VAS scores, or forward flexion. Conclusion: The presence of single or multiple allergies is not correlated with worse outcomes after primary anatomic total shoulder arthroplasty.